Tempo e música em Assim falava Zaratustra: o eterno retorno como experiência musical - Laurici Vagner Gomes (2006)
The objective of this work is to analyze the form that Nietzsche presents the idea of Perpetual Return in Thus Spoke Zarathustra, exploring, from this book published in 1884, the joint between the construction of the time problem in his previous works and the characterization of Apolo and Dioniso in The Birth of Tragedy, as well as the relation of the philosopher with the thought of Arthur Schopenhauer, who attributes to music a Metaphysical statute in the interior of the split between world as will and world as representation, and also its relation with the thought and the art of Richard Wagner, that, on the bases of metaphysics schopenhauriana musical comedy, glimpses the possibility of construction of a new knowledge system of the world through the approach between music and poetry.